Flexibility development among 5-6th grade schoolchildren under the influence of cheerleading activity - Oleksandr Aghyppo; Tetiana Bala (Kharkiv State Academy of Physical Culture, 2017)
Purpose: to determine the degree of change in the level of development of the flexibility of 5-6th grade schoolchildren under the influence of cheerleading activity. Material & Methods: 103 schoolchildren of 10-11 years took part in the research. Methods: theoretical analysis and generalization of scientific and methodological literature, pedagogical testing, pedagogical experiment and methods of mathematical statistics. Results: the indicators of the level of development of flexibility are presented, as well as the degree of their change under the influence of cheerleading activities among schoolchildren of the 5th and 6th grades of the general education school. Conclusion: the use of cheerleading activity positively influenced the degree of manifestation of the flexibility of schoolchildren of middle classes in all the parameters studied.